J2EE platform adaptation to build a monitoring and diagnostic system of AC motor faults using wavelets and TPM - Bravo Vecorena, Aland (2007)
This paper describes a research work on desing and implementation of a monitor and diagnostic prototype system to detect faults in indutrial motors using the techniques of the wavelets and methodology of total productive maintenance, all them implemented on the J2EE platform deployed over the Apache-Tomcat container. For the prototype a digital processor DSPIC30F6010A was used where is implemented the algorithm of field oriented control and the module of remote communication that uses the RS232 port to communicate with the control node through Servlets. The experimental results demonstrate that the prototype possesses flexibility and interoperability advantages compared with other existent solutions.